(untitled) (INMR - Innovation & Management Review, 2015)
This article develops a holistic model to the analysis of the main challenges of innovation management. We can analyze innovation as an issue that goes beyond the simple introduction of new ideas in the market. There is a complex interaction between people, ideas and actions. Currently, there is a greater concern with reference to understanding and systematization of types and metrics to evaluate the innovation process. However, we have left out the human aspect of the issue. How to manage innovation in an increasingly more demanding world? We suggest a model with 7 core values of innovation management, comprising strategy, learning, knowledge, confidence, creativity, culture and power. This paper is intended for academic discussion with a view to the improvement and evolution of organizational thinking in the area of innovation management. The objectives are to (1) describe the model of innovation management under a social point of view, and (2) to investigate the behavior of a company open 7 values (flexibility) and a private company (centralized). The methodology used is to build theory from case study of Eisenhardt (1989). The contribution of this paper is the formalization of a model for the analysis of innovation management. The results demonstrate that cooperation, diversity and communication are key elements for the resolution of conflicts arising from social interactions within the organization.